Streamflow variability for the Aksu River on the southern slopes of the Tien Shan inferred from tree ring records. Issue 3 (May 2016) - Zhang, Ruibo; Yuan, Yujiang; Gou, Xiaohua; Yang, Qing; Wei, Wenshou; Yu, Shulong; Zhang, Tongwen; Shang, Huaming; Chen, Feng; Fan, Ziang; Qin, Li
Abstract : Gauged river flow records from China generally span only a few decades, which hampers the detection of long-term, decadal- to centennial-scale cycles and trends in streamflow variability. New and updated tree-ring chronologies help reconstructed the water-year (October–September) streamflow for the Aksu River, which is an important river at the edge of the Taklimakan Desert that drains into the Tarim Basin. The reconstruction dates back to 1692 and has an adjusted r 2 of 0.61 (1957–2006). Based on frequency, intensity and duration of droughts and pluvial events, the lowest streamflows occurred in the 1920s. Since then streamflow has continuously increased, and was exceptionally rapidly after the 1960s, until today. The start and end of the 20th century to the present were the highest streamflow periods. The mid-20th century was the longest and driest period over the past 300 yr. The reconstructed streamflow series has a strong positive correlation with the North Atlantic Oscillation Index. Changes in mid-latitude circulation patterns influencing precipitation may have indirectly resulted in streamflow variations along the Aksu River over the past 300 yr. The rapid increase and the exceptional streamflows of the 1960s are likely linked with global warming and mid-latitude atmospheric circulation changes.